2002
DOI: 10.1007/s00221-002-1203-9
|View full text |Cite
|
Sign up to set email alerts
|

What and Where in human audition: selective deficits following focal hemispheric lesions

Abstract: A sound that we hear in a natural setting allows us to identify the sound source and localize it in space. The two aspects can be disrupted independently as shown in a study of 15 patients with focal right-hemispheric lesions. Four patients were normal in sound recognition but severely impaired in sound localization, whereas three other patients had difficulties in recognizing sounds but localized them well. The lesions involved the inferior parietal and frontal cortices, and the superior temporal gyrus in pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
73
0
3

Year Published

2007
2007
2016
2016

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 196 publications
(87 citation statements)
references
References 65 publications
10
73
0
3
Order By: Relevance
“…Auditory processing is thought to be mediated by partially segregated "what" and "where" pathways involved in sound recognition and localization, respectively (Rauschecker, 1998;Hackett et al, 1999;Clarke et al, 2000Clarke et al, , 2002Tian et al, 2001;Clarke and Thiran, 2004;De Santis et al, 2007). Previous studies have demonstrated plastic changes within the "what" stream as subjects learned to discriminate between frequency, duration, or intensity of sounds or between semantic features of complex environmental sounds or speech (Tremblay et al, 1998;Jäncke et al, 2001;Syka, 2002;Bergerbest et al, 2004;Gottselig et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…Auditory processing is thought to be mediated by partially segregated "what" and "where" pathways involved in sound recognition and localization, respectively (Rauschecker, 1998;Hackett et al, 1999;Clarke et al, 2000Clarke et al, , 2002Tian et al, 2001;Clarke and Thiran, 2004;De Santis et al, 2007). Previous studies have demonstrated plastic changes within the "what" stream as subjects learned to discriminate between frequency, duration, or intensity of sounds or between semantic features of complex environmental sounds or speech (Tremblay et al, 1998;Jäncke et al, 2001;Syka, 2002;Bergerbest et al, 2004;Gottselig et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…Regions responding to the crossmodal recognition task more than the localization task were found in the bilateral inferior occipital gyrus and the left lateral temporal cortex including the anterior part of STS and STG. However, severely deficient in auditory motion perception and partially deficient in auditory localization, but normal in recognition of environmental sounds, was accompanied with damage to a dorsal temporo-parieto-frontal region [52,53] .…”
Section: Cross-modal Studiesmentioning
confidence: 99%
“…Evidence from both monkeys and humans had already suggested that there were multisynaptic corticocortical pathways in audition paralleling those in vision (Bruce et al, 1981;Wang et al, 1995;Andersen, 1997;Romanski et al, 1999;Rauschecker and Tian, 2000;Clarke et al, 2002;Kaiser et al, 2003;Rama et al, 2004;For review see, Shroeder and Fox, 2005). The metabolic mapping study not only lends strong support to that notion, but also allows simultaneous visualization of the territory occupied by all three of these proposed pathways.…”
Section: Comparison Of Auditory and Visual Mapsmentioning
confidence: 99%